Decentralization and Governance in Indonesia 2015
DOI: 10.1007/978-3-319-22434-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Change and Corruption of Public Leaders: A Social Capital Perspective on Indonesia

Abstract: Incidents of corruption by local public leaders have increased in Indonesia in the era of a decentralized democratic regime, in which regional governments enjoy greater power and autonomy to manage regional resources. Previous research suggests that the shift of formal power from the central government to regional governments resulted in new actors at the local level becoming involved in corruption. Building on ideas from social capital theory, the current study attempts to complement previous work by analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
(85 reference statements)
0
14
1
Order By: Relevance
“…Corruption is generally defined as an Babuse of public power for private gain ( Funderburk 2012;Silitonga et al 2016;Uslaner 2008). While this general definition of corruption does not entail any particularly relational or interactional features, corruption as a phenomenon consists of a wide range of activities and some of them are intrinsically relational.…”
Section: Corruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corruption is generally defined as an Babuse of public power for private gain ( Funderburk 2012;Silitonga et al 2016;Uslaner 2008). While this general definition of corruption does not entail any particularly relational or interactional features, corruption as a phenomenon consists of a wide range of activities and some of them are intrinsically relational.…”
Section: Corruptionmentioning
confidence: 99%
“…Nepotism and cronyism are based on pre-existing relationships with relatives or friends respectively, who are installed into influential or well-paid positions despite their incompetence. Although these are just the most common forms of corruption, there are more activities which could be labelled as such (for a detailed description, see Silitonga et al 2016). What is shared by all the mentioned forms of corruption, however, is that these activities take place in human interactions and relationships.…”
Section: Corruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…31/1999 and20/2001), bribery is one the of the criminal activities classified as corruption. Furthermore, previous work has indicated that bribery is one of the most common types of corruption in the public sector in Indonesia (Silitonga et al 2016). Following Transparency International's widely used definition, we conceptualize bribery as "the offering, promising, giving, accepting or soliciting of an advantage as an inducement for an action which is illegal, unethical or a breach of trust.…”
Section: The Vignette Studymentioning
confidence: 99%
“…Despite these government initiatives, corruption is still pervasive in Indonesia, not only among appointed political leaders but also among senior civil servants in both central and local government (Silitonga et al 2016). For example, as a recent Indonesia Corruption Report (GAN Business Anti-Corruption Portal 2017) emphasizes, a corrupt judiciary, extensive bribery in the public service, and the extortion of informal payments to register businesses or obtain licenses are still rampant and perceived not only to severely harm the efficiency of business but also to undermine property rights protections and weaken dispute settlement processes.…”
mentioning
confidence: 99%